2021
DOI: 10.12982/vis.2022.017
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of plant extracts and essential oil-cyclodextrin complexes and their effect on lipid accumulation in porcine adipocytes in vitro

Abstract: Fat deposition is important for pig production because excessive fat decreases the economic value of meat production. Plant extracts have been used as feed additive in pig diets to improve oxidative stability of meat. However, only a few studies had investigated the effect of plant extracts on lipid accumulation of porcine adipocytes. Therefore, this study examined antioxidative potential of plant extracts and essential oil-cyclodextrin complexes and their effect on lipid accumulation in porcine adipocytes. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…At the same time, Yan et al (2021) indicated that supplementation of the Chinese local pig diet with tea powder had no effect on growth performance. Dietary supplementation of perilla cake, which its extract contains high levels of total phenolics and total flavonoids (Chumphukam et al, 2018), had no effect on the growth performance of finishing Thai crossbred black pigs (Sringarm et al, 2022). Several researchers have studied the use of plant extracts in growing-finishing pig diets, but no negative effects have been reported after their dietary supplementation on growth performance of those pigs (Simitzis et al, 2010;Rossi et al, 2013;Hanczakowska et al, 2015;Ranucci et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, Yan et al (2021) indicated that supplementation of the Chinese local pig diet with tea powder had no effect on growth performance. Dietary supplementation of perilla cake, which its extract contains high levels of total phenolics and total flavonoids (Chumphukam et al, 2018), had no effect on the growth performance of finishing Thai crossbred black pigs (Sringarm et al, 2022). Several researchers have studied the use of plant extracts in growing-finishing pig diets, but no negative effects have been reported after their dietary supplementation on growth performance of those pigs (Simitzis et al, 2010;Rossi et al, 2013;Hanczakowska et al, 2015;Ranucci et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the studies of Ko et al (2008) andRossi et al (2014), a substantial effect of pig diets on pork's lipid oxidation was observed after 3 d of storage at 4 °C. Green tea extract contains high total phenolic and total flavonoid levels (Norkeaw et al, 2022). These substances are regarded as possessing high antioxidant ability due to the redox characteristics of phenolic compounds, which are strong reducing agents via hydrogen donors and radical scavengers (Weerawatanakorn et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation